Functions Of Forensic Psychologists In Criminal Justice System - Obi-Nwosu, Harry; Umeaku, Ndubuisi N; Nkot, Baleguel F (Practicum Psychologia, 2018)
The paper examined the functions of Forensic Psychologists in the legal system which includes: expert witness, trial consultancy, malingering evaluation, competency evaluation and sanity evaluation. It further x- rayed the effects of their absence within the criminal justice system and emphasized that when these functions are absent within the criminal justice system due to the non-recognition of the functions of these experts, the effects are always enormous and affects all the stakeholders in the system. These effects include: frustration, delay of justice, anger, stress, betrayal and confusion among others. The stakeholders that are grossly affected are: the accused, victims, judicial officers and the police. The paper concluded by recommending that Forensic Psychologists should be employed in our criminal justice system in order to ameliorate these effects and ensure a better and refined criminal justice system comparable to its counterparts in the comity of nations.